2006
DOI: 10.1897/05-628r.1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity of polycyclic aromatic compounds to the springtail Folsomia candida and the enchytraeid Enchytraeus crypticus

Abstract: An urgent need exists for incorporating heterocyclic compounds and (bio)transformation products in ecotoxicological test schemes and risk assessment of polycyclic aromatic compounds (PACs). The aim of the present study therefore was to determine the chronic effects of (heterocyclic) PACs on two terrestrial invertebrates, the springtail Folsomia candida and the enchytraeid Enchytraeus crypticus. The effects of 11 PACs were determined in chronic experiments using reproduction and survival as endpoints. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 42 publications
(63 reference statements)
10
57
0
Order By: Relevance
“…Consequently, deviations from the relationship between effect concentrations and K ow values may indicate a different mode of action (Bearden and Schultz, 1998;Escher et al, 2005). This was clearly demonstrated previously for soil invertebrates chronically exposed to several PACs (Sverdrup et al, 2001;Droge et al, 2006), and therefore in the present study we followed the same approach. Since for the tested compounds, having a logK ow value <5, porewater exposure of the midge larvae was expected (Belfroid et al, 1996), chronic LC 50 values (mM) were calculated from the chronic sediment LC 50 values (mmol/kg sediment d.w., Table 2), using a set of empirically determined organic carbon-water partition coefficients (K oc ) from (Jonassen, 2003;Jonassen et al, 2003) and correcting for the organic carbon content of the sediment.…”
Section: Narcosis Versus Specific Effectsmentioning
confidence: 66%
See 2 more Smart Citations
“…Consequently, deviations from the relationship between effect concentrations and K ow values may indicate a different mode of action (Bearden and Schultz, 1998;Escher et al, 2005). This was clearly demonstrated previously for soil invertebrates chronically exposed to several PACs (Sverdrup et al, 2001;Droge et al, 2006), and therefore in the present study we followed the same approach. Since for the tested compounds, having a logK ow value <5, porewater exposure of the midge larvae was expected (Belfroid et al, 1996), chronic LC 50 values (mM) were calculated from the chronic sediment LC 50 values (mmol/kg sediment d.w., Table 2), using a set of empirically determined organic carbon-water partition coefficients (K oc ) from (Jonassen, 2003;Jonassen et al, 2003) and correcting for the organic carbon content of the sediment.…”
Section: Narcosis Versus Specific Effectsmentioning
confidence: 66%
“…In those acute high-dose experiments, narcosis was the main mode of action. The lower limit for narcosis was estimated by dividing the acute LC 50 values from the LC 50 elogK ow relationship by a factor of 3, because in previous studies on soil invertebrates a LC 50 / EC 50 ratio larger than 3 suggested sublethal effects of the tested compounds on reproduction, deviating from narcosis (Droge et al, 2006). Hence, we assumed that specific effects on emergence occurred if the effect concentrations obtained in the present study were below the calculated lower limit for narcosis.…”
Section: Narcosis Versus Specific Effectsmentioning
confidence: 89%
See 1 more Smart Citation
“…This generalization is obviously a big step forward, but the same study demonstrated that specific modes of action other than narcosis caused strong deviations from the relationship between toxicity and logK ow (Bleeker et al, 2002a). Such specific modes of action may even cause closely related compounds, such as isomers, to differ several orders of magnitude in toxicity (Walton et al, 1983;Wood et al, 1983;Kraak et al, 1997;Wiegman et al, 2001;Bleeker et al, 2002a;Droge et al, 2006;León Paumen et al, 2008a). Comparative toxicity is further complicated by the repeated observations that transformation products, generated with the aim to detoxify the parent compound, may have an unexpected and sometimes even exceptionally high toxicity.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In many short-term high-dose PAC toxicity studies, including those mentioned above, mortality was used as endpoint. This ignores that PACs can exert sublethal effects during long-term exposure, therewith affecting different biological endpoints (Droge et al, 2006;Feldmannova et al, 2006;León Paumen et al, 2008a). Hence, a reliable hazard assessment for PACs requires the inclusion of biological endpoints other than mortality, such as chronic effects on growth and reproduction.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%